Optimization and validation of an RP-HPLC method for the estimation of 6-mercaptopurine in bulk and pharmaceutical formulations - Vanita Somasekhar (Universidade de São Paulo, 2014)
A reverse phase HPLC method is described for the determination of 6-mercaptopurine in bulk and tablets. Chromatography was carried on a C18 column using a mixture of acetonitrile and 0.05 mol/L sodium acetate buffer (10:90 v/v) as the mobile phase at a flow rate of 1 mL/min-1 with detection at 324 nm. The retention time of the drug was 3.25 min. The detector response was linear in the concentration of 0.01-5 μg/mL. The limit of detection and limit of quantification were 17 and 52 ng/mL respectively. The method was validated by determining its sensitivity, linearity, accuracy and precision. The proposed method is simple, economical, fast, accurate and precise and hence can be applied for routine quality control of mercaptopurine in bulk and tablets.